Evaluation of Trace Mineral Sources on Newly Arrived Stocker Cattle - C. S. Weibert; W. R. Hollenbeck; S. B. Laudert; J. D. Kubick; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2017)
Light weight stocker calves experience variable degrees of physiological and psychological stressors as they are assembled from various marketing points and transported to their destination. Susceptibility to disease in young, long hauled calves is greatly enhanced and the consequence of sickness is a major cause for poor production outcomes. Enhanced nutritional trace mineral programs that contain zinc, copper, and manganese from organic or hydroxy sources may be more efficacious as a means of minimizing disease or realizing improved performance than the sulfate form of these respective trace minerals.
Keywords: trace minerals; stocker; drylot